First Blood: How Three Generations of Newfoundland Women Learned about Menstruation - Porter, Marilyn (Atlantis, 2006)
This article discusses how girls in Newfoundland learn about and experience menstruation. The project focussed on three generations of women, and we found differences, over time, in how appropriate knowledge is acquired by young girls and how the event of menarche is experienced and interpreted.